A atuação e os desafios dos bacharéis em gerontologia: percepções de profissionais de uma equipe de medicina preventiva - Bortoletto-Santos, Laís Rita (2019)
Gerontology is a science that studies the aging process in the biopsychosocial dimensions of multi and interdisciplinary scope as well as it can contribute to search for new health care practices for the elderly in Brazilian society. However, there are few professionals graduated in Gerontology compared to the number of elderly in Brazil. Therefore, in this study, the objective was to identify the challenges of this new profession from the perception of a multidisciplinary Preventive Medicine team. Data acquisition was made from a case study and a semi-structured questionnaire, approaching a qualitative perspective. Atlas-ti Software was used for results analysis, since this tool helps in the systematic organization of data. The analysis of the results showed that there are common and specific challenges in the assistance and management areas, listed as overcoming barriers. Among the common challenges, we can highlight the building of the profession's essential attributions with the team as well as achieving the profession's recognition by meeting the stakeholders expectations in care and management. Regarding the care area, challenges can be presented to clarify their holistic view of the care process and to highlight their ability to insert themselves in other health services. In the management area, the main challenges observed were to highlight the particularities of the gerontologist's performance in managing organizations that serve the elderly, meet the growing demand and diversity of the elderly population, and be prepared to manage larger teams. Finally, the team pointed out the broad performance of the gerontologist in the health area, including activities relevant to their skills and competencies such as developing and executing preventive projects, performing gerontological assessments, dance and memory workshops, monitoring patients, supervise and guide multidisciplinary teams, manage and discuss cases with the team, coordinate continuing education activities, promote quality care, among others.